PERAMALAN TINGGI GELOMBANG BERDASARKAN KECEPATAN ANGIN DI PERAIRAN PESISIR SEMARANG MENGGUNAKAN MODEL FUNGSI TRANSFER (Studi Kasus Bulan Januari 2014 sampai dengan Desember 2014) - Firda Megawati; Rita Rahmawati; Suparti Suparti (Jurnal Gaussian, 2015)
Semarang coast is suitable to develop marine transport activities such as sailing because of its strategic location in the coastal region of Indonesia. The condition of sailing in Indonesia is said smoothly if wave height is in the normal range which is 1-2 meters. Therefore, there will be research to predict wave height in Semarang harbor by using transfer function. The data used is secondary data from BMKG of Semarang period January 2014 to December 2014 with the variable X as the average daily of wind speed and variable Y as average daily of wave height. Model that formed based on the input wind speed is ARIMA(2,1,0) while transfer function model that formed is b=0, s=0, and r=0 with noise model ARMA(1,1). The forecasting results for January 2015 show that the wave height tends to rise and the highest wave is on the third day with 0,9589 meters. Calculation accuracy of forecasting wave heights using transfer function model with MAPE produce a value of 18,7%. Keywords : Transfer Function, Wave Height, Wind Speed.